A Defense of Presentist Time Travel - Zhuang, Xuanpu (Filozofia Nauki, 2022)
Presentism usually holds that only present entities exist. In contrast to presentism, eternalism holds that past, present, and future entities all exist. According to some philosophers, presentism is intuitively incompatible with time travel. In this paper, I defend the compatibility between presentism and time travel by arguing for a plausible account of causation in the presentist framework. To achieve my goal, I respond to an objection to presentist time travel that is based on the nonexistence of the past: the Causation Objection. According to the Causation Objection, causal relations between objects at different times are necessary for time travel, but these are impossible for presentists. I evaluate a possible reply based on a non-relational account of causation and show that this reply is not satisfying. Subsequently, I put forward a fact-based account of causal relation. I argue that presentists could accept facts instead of events as causal relata, thus establishing causal relations. As all facts about the past, the present, and the future exist in the present, we could explain how backward causation works and describe the discrepancy between personal time and external time in presentist time travel; in this way, I argue, we could vindicate the compatibility between presentism and time travel.